2005
DOI: 10.1136/bmj.38601.447731.55
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of prevention of falls in people aged ≥75 with severe visual impairment: the VIP trial

Abstract: Objectives To assess the efficacy and cost effectiveness of a home safety programme and a home exercise programme to reduce falls and injuries in older people with low vision. Design Randomised controlled trial. Setting Dunedin and Auckland, New Zealand. Participants 391 women and men aged ≥ 75 with visual acuity of 6/24 or worse who were living in the community; 92% (361 of 391) completed one year of follow-up. Interventions Participants received a home safety assessment and modification programme delivered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
362
1
31

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(399 citation statements)
references
References 24 publications
5
362
1
31
Order By: Relevance
“…In the only randomized controlled trial to date that evaluates fall-prevention interventions among older adults with vision impairment, investigators reported that, of the two interventions examined, a home safety intervention (e.g., increasing illumination, removing throw rugs, etc. ), but not a strength and balance training program, significantly reduced falls among persons with vision impairment aged ≥75 years in New Zealand (8).…”
Section: Discussionmentioning
confidence: 88%
“…In the only randomized controlled trial to date that evaluates fall-prevention interventions among older adults with vision impairment, investigators reported that, of the two interventions examined, a home safety intervention (e.g., increasing illumination, removing throw rugs, etc. ), but not a strength and balance training program, significantly reduced falls among persons with vision impairment aged ≥75 years in New Zealand (8).…”
Section: Discussionmentioning
confidence: 88%
“…rehabilitation of PD patients. It plays an important role in the prevention of injuries caused by falls which are an important issue directly related to PD [21][22][23][24][25][26]. Lord and Dayhew [27] showed that people with impaired sight fall more often than people with normal vision capability.…”
Section: Discussionmentioning
confidence: 99%
“…Um das Sturzrisiko im häuslichen Umfeld einzuschätzen, wurde in drei Studien das "Westmead Home Safety Assessment" (WeHSA), welches von Clemson (1997) entwickelt wurde, eingesetzt Lannin et al, 2007;Pighills et al, 2011). Darüber hinaus wurden zur Erfassung von Sturzrisikoquellen in der Häuslichkeit Checklisten eingesetzt (Clemson, Roland, & Cumming, 1992;Stevens, Holman, Bennett, & De Klerk, 2001;Pardessus et al, 2002;Lin et al, 2007 (Clemson, 1997;Stevens et al, 2001;Campbell et al, 2005;Lannin et al, 2007;Pighills et al, 2011) vor dem Hintergrund von Kontext-und organisatorischen Rahmenbedingungen in Deutschland in die Praxis implementiert und die Akzeptanz der teilnehmenden Therapeuten/-innen wie auch der Betroffenen maximiert werden kann. Dabei sollen konkrete Maßnahmen zur Sicherstellung der Übertragungsqualität der Intervention in der praktischen Umsetzung erprobt werden.…”
Section: Evidenzlageunclassified